Impact of Motivation on Performance: The Role of Organizational Commitment - Mochammad Munir Rachman (Jurnal Manajemen Teori dan Terapan, 2022)
Objective: The study aims to analyze the important role of motivation in improving the performance of company employees with the support of organizational commitment as a mediation.